2022
DOI: 10.18103/mra.v10i8.3041
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Using the Right Tools at the Right Time

Abstract: COVID-19, caused by SARS-CoV2, first described in several cases of pneumonia in Wuhan, China in December 2020 has now become a disease that is now present throughout the world. Multiple evidence-based measures and therapeutics are now available for the prevention and treatment of COVID-19. Many therapeutics have been studied and some even continue to be used without compelling evidence to suggest efficacy. Critical to the prevention and successful identification of treatments for COVID-19 has been an apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Since the early phases of the pandemic, corticosteroids (specifically dexamethasone) have been considered a milestone in the treatment of hospitalized COVID-19 patients receiving respiratory support ( Peter et al, 2021 ). Studies showed that it is crucial to administer steroids during the early inflammatory phase (i.e., around the second week of illness) to reduce the risk of disease progression and death ( Griffin, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early phases of the pandemic, corticosteroids (specifically dexamethasone) have been considered a milestone in the treatment of hospitalized COVID-19 patients receiving respiratory support ( Peter et al, 2021 ). Studies showed that it is crucial to administer steroids during the early inflammatory phase (i.e., around the second week of illness) to reduce the risk of disease progression and death ( Griffin, 2022 ).…”
Section: Introductionmentioning
confidence: 99%